Centennial garden ‘the smart way for green planting’ - Zanuddin, Nurhazwani; Shahudin, Fakharudin; Jaballudin, Norazura (Universiti Teknologi MARA, Kedah, 2023)
Today, Malaysian agriculture uses too many chemicals, water, and space. Unfortunately, cropyields are damaged and of poor quality due to the uncontrolled use of chemical pesticides on ecosystems. In addition, the growing population size has contributed to the increase in domesticwaste such as food waste, plastic waste, toxic waste and so on. Thus, the Centennial Garden innovation project, was inspired to a smaller scale by focusing on excess food waste and limitedspace for planting activities. Centennial Park is an innovation for improvements to all of the problems mentioned earlier. The purpose of this Centennial Garden is to harvest nature’s bio by using food waste as bio compost, hand washing water to avoid water wastage. In addition, we reused plastic bottles as base pots for planting, and our garden was designed using the vertical garden method. The combination of these elements will save space, improve the qualityof gardening in the school, and be able to avoid wastage of plastic bottles around the school. In addition, we combined two crop systems called fertigation and hydroponics into one systematic system for crops.